2019
DOI: 10.3390/ijms20236048
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Activity of Blood Acid Sphingomyelinase in the Course of Multiple Myeloma

Abstract: Acid sphingomyelinase (aSMase) is involved in the generation of metabolites that function as part of the sphingolipid signaling pathway. It catalyzes the breakdown of sphingomyelin into ceramide, a bioactive lipid that, among other roles, is involved in regulation of apoptosis. Dry drop blood test (DBS) and colorimetric 2-step enzymatic assay were used to assess the activity of human blood aSMase, beta-galactosidase, and beta-glucosidase, these enzymes are lysosomal hydrolases that catalyze the degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Of note and surprisingly, sphingosine, sphinganine, and ceramide levels were found to be higher in AML samples, with a ceramide/S1P ratio significantly higher in AML patient samples compared to control samples [ 187 ]. Similar changes in sphingosine, sphinganine, and ceramide levels were also found in blood samples from patients with multiple myeloma [ 188 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 54%
See 2 more Smart Citations
“…Of note and surprisingly, sphingosine, sphinganine, and ceramide levels were found to be higher in AML samples, with a ceramide/S1P ratio significantly higher in AML patient samples compared to control samples [ 187 ]. Similar changes in sphingosine, sphinganine, and ceramide levels were also found in blood samples from patients with multiple myeloma [ 188 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 54%
“…Indeed, exosomes that were high in aSMase were able to confer resistance to cells that were previously responsive to treatment [ 370 ]. However, while analysis of blood samples from multiple myeloma patients showed that ceramide, sphingosine, and sphinganine levels were significantly higher in these patients compared to healthy patients [ 188 ], aSMase activity was significantly lower [ 188 ]. ASMase activation has been also implicated in the induction of cell death by the major polyphenol in green tea extract, EGCG [(−)-epigallocatechin-3-O-gallate] [ 348 , 371 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway can contribute to cell growth, division, and survival of cancer cells (Fig. 1) [15, 30, 34-36].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a possible role for ASM in MM development. Although these results require further analysis and better understanding of their meaning in the context of MM pathogenesis, they point out a possible diagnostic value for ASM levels ( 149 ).…”
Section: Bm Microenvironment Cellular Components Release Sphingolipid...mentioning
confidence: 99%